Inactivation of the cyclin-dependent kinase Cdc28 abrogates cell cycle arrest induced by DNA damage and disassembly of mitotic spindles in Saccharomyces cerevisiae. - Li, X (1997)
Eukaryotic cells may halt cell cycle progression following exposure to certain exogenous agents that damage cellular structures such as DNA or microtubules. This phenomenon has been attributed to functions of cellular control mechanisms termed checkpoints. Studies with the fission yeast Schizosaccharomyces pombe and mammalian cells have led to the conclusion that cell cycle arrest in response to inhibition of DNA replication or DNA damage is a result of down-regulation of the cyclin-dependent kinases (CDKs). Based on these studies, it has been proposed that inhibition of the CDK activity may constitute a general mechanism for checkpoint controls. Observations made with the budding yeast Saccharomyces cerevisiae, however, appear to disagree with this model. It has been shown that high levels of mitotic CDK activity are present in the budding yeast cells arrested in G2/mitosis as the result of DNA damage or replication inhibition. In this report, we show that a novel mutant allele of the CDC28 gene, encoding the budding yeast CDK, allowed cell cycle passage through mitosis and nuclear division in the presence of DNA damage and the microtubule toxin nocodazole at a restrictive temperature. Unlike the checkpoint-defective mutations in CDKs of fission yeast and mammalian cells, the cdc28 mutation that we identified was recessive and resulted in a loss of the CDK activity, including the Clb2-, Clb5-, and Clb6-associated, but not the Clb3-associated, CDK activities. Examination of several known alleles of cdc28 revealed that they were also, albeit partially, defective in cell cycle arrest in response to UV-generated DNA damage. These findings suggest that Cdc28 kinase in budding yeast may be required for cell cycle arrest resulting from DNA damage and disassembly of mitotic spindles.